2019
DOI: 10.1177/0956462419832750
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C care cascade in HIV patients at an urban clinic in the early direct-acting antiviral era

Abstract: Guidelines advocate universal, prompt treatment of hepatitis C (HCV) infection in HIV/HCV co-infected patients, but barriers to uptake of HCV direct-acting antivirals (DAAs) remain unclear in this population. This retrospective study investigated the care cascade from HCV diagnosis to sustained virologic response (SVR) at an urban infectious disease clinic in Saint Louis, Missouri during the first 18 months of interferon-free DAA availability in the United States. Of 1949 HIV patients seen in clinic, 91.9% wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 44 publications
2
19
2
Order By: Relevance
“…Early studies among both HCV‐monoinfected and HIV/HCV‐coinfected patients found that Hispanic Whites and Blacks were less likely to be treated 21,24,30–32 . Our finding of a lack of race/ethnicity‐based effect modification in the overall cohort is similar to more recent studies, which may be explained by the changing treatment environment, with more aggressive treatment of HIV/HCV‐coinfected patients 22,23 …”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Early studies among both HCV‐monoinfected and HIV/HCV‐coinfected patients found that Hispanic Whites and Blacks were less likely to be treated 21,24,30–32 . Our finding of a lack of race/ethnicity‐based effect modification in the overall cohort is similar to more recent studies, which may be explained by the changing treatment environment, with more aggressive treatment of HIV/HCV‐coinfected patients 22,23 …”
Section: Discussionsupporting
confidence: 82%
“…Our finding that a history of substance use was associated with a decreased likelihood of DAA prescription is consistent with previous studies. 23,24 The decreased likelihood of DAA prescriptions among patients with a history of substance use might reflect provider reluctance as a result of concern about non-adherence,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insurance prior authorizations have been a major barrier to HCV treatment in the DAA era, with frequent insurance denial of treatment requiring appeal [ 48 ], diversion of clinical staff time to insurance paperwork [ 49 ], and delays between time of prescription and approval [ 50 ]. Together, these logistical barriers to medication access place a significant burden on staff that may limit clinics’ ability to institute and scale up HCV treatment [ 49 ].…”
Section: Discussionmentioning
confidence: 99%